2002
DOI: 10.1021/ja028442t
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Methyl Transfer Kinetics of the α Subunit from Acetyl Coenzyme A Synthase

Abstract: RECEIVED DATE (will be automatically inserted after manuscript is accepted)Acetyl-coenzyme A synthase is a bifunctional enzyme found in anaerobic archaea and bacteria that grow autotrophically on simple inorganic compounds such as CO 2 /H 2 or CO. The enzyme from Moorella thermoacetica (ACS) is an α 2 β 2 tetramer containing two unique Ni-Fe-S active sites connected by a molecular tunnel. 1,2 The Ni 1 Fe 4 S 4-5 C-cluster catalyzes the reversible reduction of CO 2 to CO and is located in the β subunit. CO gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 9 publications
0
48
0
Order By: Relevance
“…It is important to design experiments that would identify the one-electron shuttle in the synthesis. This is intriguing, since stopped-flow studies suggest that the most likely candidate, the [Fe 4 S 4 ] component of the A cluster, is not involved in redox reactions during the synthesis (32).…”
Section: Demonstration That Acetyl-coa Synthesis Involves Random Addimentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to design experiments that would identify the one-electron shuttle in the synthesis. This is intriguing, since stopped-flow studies suggest that the most likely candidate, the [Fe 4 S 4 ] component of the A cluster, is not involved in redox reactions during the synthesis (32).…”
Section: Demonstration That Acetyl-coa Synthesis Involves Random Addimentioning
confidence: 99%
“…On the other hand, Barondeau and Lindahl (8) proposed that methylation of ACS is the first step in an ordered mechanism of acetyl-CoA synthesis because the methyl group of the CH 3 -CFeSP could be transferred to CODH⅐ACS (in the absence of CO), forming a methylated enzyme that, when treated with CO and CoA, forms acetyl-CoA. That methylation of CODH⅐ACS or recombinant (ACS HT ) (31,32) by CH 3 -CFeSP occurs faster than acetyl-CoA synthesis also suggests that methylation is the first step in the synthesis (33). Furthermore, CO acts as a substrate inhibitor of acetyl-CoA synthesis (34,35).…”
mentioning
confidence: 99%
“…Although recent studies have indicated that electron flow to and from the Fe 4 S 4 cluster is too slow compared to the rate of methyl transfer, 46 the proposed mechanisms of ACS activity mostly involve redox changes at the Fe 4 S 4 cluster during key steps of the catalytic cycle. 5,6,47,48 Theoretical studies suggest that the Ni(0) state 49 is only stabilized by either removal of the cluster 15 or by the presence of a neighboring reduced iron-sulfur cluster [Fe 4 S 4 ] 1+ (S = ½).…”
Section: Reactivity Of Ni-ni Modelsmentioning
confidence: 99%
“…13 Therefore, it has been postulated that reductive activation begins with the CO-dependent reduction of the CODH C cluster that then transfers an electron to the [Fe 4 S 4 ] 2+ cluster of the CFeSP, which reduces the bound Factor III m to the Co 1+ state. 14,15,80 Reduction activation is enhanced by replacement of the lower axial MBI ligand of Factor III m by a weaker water ligand when the cofactor binds to the CFeSP, generating a fivecoordinate Co 2+ species that resembles Co 2+ Cbi + (see above). This ligand switch has a profound influence in the redox properties of the Co center, increasing the Co 2+/1+ reduction potential by ~120 mV relative to that of the MBI-bound form of the cofactor found in solution (~−620 mV).…”
Section: Reactivation Of Co 2+ Cfespmentioning
confidence: 99%